KORELASI ANTARA KADAR INTERLEUKIN-6 DENGAN PROFIL TROMBOSIT PADA PENDERITA SIROSIS HATI - , DR. DEWI WIDYASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Cirrhosis is the ninth leading cause of death in the United States and is responsible for 1.2% of all US deaths. In Indonesia the prevalence of data of liver cirrhosis does not exist yet, just the reports from several educational centers only. In Dr. Sardjito hospital Yogyakarta, the number of patients with liver cirrhosis ranges from 4,1% of patients whom treated at the Department of Internal Medicine within 1 year (2004). Liver disease is associated with a variety of haemostatic abnormalities that disrupt the delicate balance between clotting and fibrinolysis, abnormalities in both platelet number and platelet function are common in chronic liver disease. Platelet profile (platelet count, mean platelet volume/MPV, and platelet distribution width/PDW) may be used for the diagnosis and differentiation of several pathologies, and MPV might help in the assessment of fibrosis in patients with chronic liver disease. Interleukin-6 is a pleiotropic cytokine with many immunologic and metabolic reactions, is generally regarded as an important cytokine in the cytokine networks that regulate immunologic reactions and acute phase response. A relationship between IL-6 and fibrosis/liver cirrhosis have also been reported previously. This study aimed to determine the correlation between the levels of IL-6 and a profile of platelets in patients with liver cirrhosis. Subjects were patients with liver cirrhosis who are hospitalized or outpatient of Department of Internal Medicine in Dr. Sardjito hospital Yogyakarta since July 2010 up to the number of samples met, who met the inclusion criteria. Research subjects is taken in sequence until the number of samples met. All study subjects agreed to follow the study and signed an informed consent. The results will be analyze by a computerization using the Pearson correlation test to determine the correlation levels of IL-6 and profile of platelets in all samples when the data are normally distributed. When data are not normally distribute, the Spearman correlation test will be used. The magnitude of correlation is given by ârâ. The p-value is significant if p<0,05.